Estimating bank of Ghana's policy responses in the context of Taylor rule: Is the inflation target realistic? - Abdul-Aziz Iddrisu; Imhotep Paul Alagidede (Cogent Economics & Finance, 2021)
Although literature acknowledges the nonlinearity in monetary policy behaviour of central banks, the appropriateness of the models used to capture the nonlinearity remains questionable. Moreover, the paucity of research on nonlinear monetary policy rules in the context of Africa and Ghana in particular is worrying, given the numerous breaches of the publicly announced inflation targets. The study estimates the Bank of Ghana's policy responses over the inflation targeting period using the Taylor rule. We find that the Bank of Ghana reacts asymmetrically to inflation gap below and above the estimated inflation threshold of 16.4% with considerable inflation accommodation instead of targeting it. We question the logic behind the prevailing upper and lower bounds inflation target given the evidence to the contrary. The average inflation over the targeting period, the estimated inflation threshold and the structure of the Ghanaian economy raise questions of feasibility of achieving the inflation target on sustainable basis. Policy implications are discussed.
Keywords: 330; Inflation Targeting; Monetary Policy Rule; Sample Splitting; Threshold